Drosophila adiponectin receptor in insulin producing cells regulates glucose and lipid metabolism by controlling insulin secretion. - Kwak, S.J.; Hong, S.H.; Bajracharya, R.; Yang, S.Y.; Lee, K.S.; Yu, K. (PLoS ONE, 2013)
Adipokines secreted from adipose tissue are key regulators of metabolism in animals. Adiponectin, one of the adipokines, modulates pancreatic beta cell function to maintain energy homeostasis. Recently, significant conservation between Drosophila melanogaster and mammalian metabolism has been discovered. Drosophila insulin like peptides (Dilps) regulate energy metabolism similarly to mammalian insulin. However, in Drosophila, the regulatory mechanism of insulin producing cells (IPCs) by adipokine signaling is largely unknown. Here, we describe the discovery of the Drosophila adiponectin receptor and its function in IPCs. Drosophila adiponectin receptor (dAdipoR) has high homology with the human adiponectin receptor 1. The dAdipoR antibody staining revealed that dAdipoR was expressed in IPCs of larval and adult brains. IPC- specific dAdipoR inhibition (Dilp2>dAdipoR-Ri) showed the increased sugar level in the hemolymph and the elevated triglyceride level in whole body. Dilps mRNA levels in the Dilp2>dAdipoR-Ri flies were similar with those of controls. However, in the Dilp2>dAdipoR-Ri flies, Dilp2 protein was accumulated in IPCs, the level of circulating Dilp2 was decreased, and insulin signaling was reduced in the fat body. In ex vivo fly brain culture with the human adiponectin, Dilp2 was secreted from IPCs. These results indicate that adiponectin receptor in insulin producing cells regulates insulin secretion and controls glucose and lipid metabolism in Drosophila melanogaster. This study demonstrates a new adipokine signaling in Drosophila and provides insights for the mammalian adiponectin receptor function in pancreatic beta cells, which could be useful for therapeutic application.